New and bioactive polyketides from Hawaiian marine-derived fungus Trichoderma sp. FM652. Issue 23 (1st December 2022) - Zaman, KH Ahammad Uz; Wu, Xiaohua; Sarotti, Ariel M.; Cao, Shugeng
Abstract: Two new sorbicillinoid derivatives (1 and 2 ), together with ten other related compounds (3–12 ) were isolated from a Hawaiian marine fungal strain Trichoderma sp. FM652. The structures of compounds 1 and 2, including the absolute configuration, were elucidated by extensive analysis of NMR spectroscopy, HRESIMS and electronic circular dichroism (ECD) data. Compounds 6–12 exhibited significant anti-proliferative activity against ovarian cancer cell line A2780, with the IC50 values ranging from 0.5 to 8.07 μM. Moreover, compounds 1, 7 and 8 showed significant inhibition against NF-κB with IC50 values of 13.83, 24.40 and 14.63 µM, respectively. Compounds 6, 9 and 12 also demonstrated moderate inhibitory activity against S. aureus and methicillin resistant S. aureus with the MIC values in the range of 10–40 μg/mL. Graphical Abstract: UF0001